Zinc ions enhance tolerance to nanoplastics stress in rice seedlings: Advancing the development and optimization of traditional zinc fertilizers - Jia Liu; Yang Guo; Yanan Gao; Xi Chen; Lunyan Wang; Xiangqian Jia; Zhonghua Zhang; Xiaorui Guo; Yang Liu (Ecotoxicology and Environmental Safety)
Microplastic pollution threatens sustainable agriculture. Zinc (Zn), an essential micronutrient, plays a key role in crop growth and stress responses. While zinc oxide nanoparticles (ZnO NPs) mitigate microplastic toxicity in rice, their long-term use poses environmental risks. Zinc sulfate (ZnSO₄) is a traditional Zn fertilizer, but its interaction with microplastics remains unclear. This study treated rice seedlings with polystyrene (PS) microplastics and ZnSO₄ to assess their effects on growth, Zn uptake, and stress response mechanisms. PS exposure inhibited growth, impaired photosynthesis, reduced stomatal conductance, and induced ROS accumulation, causing oxidative stress that damaged cells and disrupted metabolism, while activating antioxidant enzymes. It also reduced Zn content and altered metabolite accumulation, affecting growth regulation. Appropriate Zn levels alleviated PS toxicity via distinct mechanisms: in shoots, Zn optimized nitrogen metabolism to restore photosynthesis, while in roots, it regulated carbon metabolism to reduce ROS and enhance development. The findings indicate that zinc enhances rice tolerance to microplastic stress by revealing organspecific mechanisms through which traditional zinc fertilizers exert their alleviating effects, providing both mechanistic insight and scientific evidence to optimize their application. This study also offers a viable alternative to reduce the environmental risks associated with ZnO nanoparticles, thereby promoting greener and more sustainable agricultural development.